Ethical and passive leadership and their joint relationships with burnout via role clarity and role overload - Vullinghs, Jesse T. (Journal of business ethics, 2020)
Burnout has important ramifications for employees and organizations and preventing burnout forms an ethical issue for managers. However, the role of the leader and especially the role of ethical aspects of leadership have received relatively little attention in relation to burnout to date. We conducted a survey among employees (N = 386) of a Dutch retail organization, nested in 122 teams with a leader. Our first contribution is that we empirically show the hypothesized opposing relationships of ethical and passive leadership behavior with follower burnout. Furthermore, we examined two job characteristics as mechanisms that link these forms of leadership and burnout. Lastly, we show that the positive relationship of ethical leadership with burnout via role clarity (but not overload) is dependent on the degree of passive leadership the leader is perceived to display. Our results suggest that organizations should promote ethical leadership behaviors and limit passive leadership behaviors by stimulating leaders to be active in their role and use their social influence to promote ethical conduct.